Foliar Zinc Application to Wheat May Lessen the Zinc Deficiency Burden in Rural Quzhou, China - Yu, Bao-Gang; Liu, Yu-Min; Chen, Xiu-Xiu; Cao, Wen-Qing; Ding, Tong-Bin; Zou, Chun-Qin (Frontiers in Nutrition, 2021)
Zinc (Zn) malnutrition is a common health problem, especially in developing countries. The human health and economic benefits of the replacement of conventional flour with Zn-biofortified wheat flour in rural household diets were assessed. 145 wheat flour samples were collected from rural households in Quzhou County. Then, field experiments were conducted on wheat at two Zn levels (0% and 0.4% ZnSO4·7H2O foliar application) under 16 diverse agricultural practices in Quzhou County. Foliar Zn application significantly increased the Zn concentration and bioavailability in wheat grain and flour. If rural households consumed Zn-biofortified flour instead of self-cultivated flour or flour purchased from supermarkets, 257-769 or 280-838, 0.46-1.36 million or 0.50-1.49 million disability-adjusted life years (DALYs) lost, respectively, could be saved in Quzhou County and China. Amounts of 2.3-12.0 million and 5.5-22.6 billion RMB could be obtained via Zn-biofortified flour in Quzhou County and China, respectively. The current study indicates that Zn-biofortified flour via foliar Zn application is a win-win strategy to maintain the yield and combat human Zn deficiency in rural households in China. More health and economic benefits could be obtained in rural household dependent on wheat flour purchased from supermarkets than in those dependent on self-cultivated wheat flour.